Genomic analysis of dengue virus serotype 1 (DENV-1) genotypes from Surabaya, Indonesia - Benediktus Yohan, - (Springer Netherlands, 2018)
Dengue has caused a significant public health impact globally. With the diverse genetic of the causative viruses, analysis of dengue virus (DENV) genomes is important to supplement epidemiological data with information that can be used to reconstruct the history of epidemics in time and space. We have reported the clinical and virological characteristics of dengue in Surabaya, Indonesia and revealed the presence of all four DENV serotypes and the predominance of DENV-1. The further classification of Surabaya DENV-1 into two different genotypes warrants in-depth genomic analysis to study the dynamics of both genotypes and their contribution to virus evolution, virus transmission, and disease. We performed full-length genome sequencing to nine isolates’ representatives from DENV-1 Genotype I and Genotype IV. Phylogenetic and evolutionary analyses suggested the more recent introduction of Genotype I viruses compared to the more endemic Genotype IV. Comparative analysis of Surabaya DENV-1 genomes and other sequences available publicly revealed that the majority of the DENV-1 codons were under strong purifying selection, while seven codon sites identified to be under positive selection. We highlight a unique codon site under the positive pressure in the NS1 gene of DENV-1. Our results provide additional genomic data of DENV from Indonesia that may contribute to the better understanding of dengue disease dynamics.